VD_FINDINFO ML / 2016 / 87 vom 30. März 2016 - VD Tribunal cantonal (2016)
DROIT D'ÊTRE ENTENDU, DROIT D'ÊTRE PRÉSENT À L'AUDIENCE, REPORTDÉPLACEMENT | 29 al. 2 Cst., 84 LP, 135 CPC (CH), 253 CPC (CH)